2003
DOI: 10.1161/01.str.0000080935.01264.91
|View full text |Cite
|
Sign up to set email alerts
|

Very Early Risk of Stroke After a First Transient Ischemic Attack

Abstract: Background and Purpose-The commonly quoted early risks of stroke after a first transient ischemic attack (TIA)-1% to 2% at 7 days and 2% to 4% at 1 month-are likely to be underestimates because of the delay before inclusion into previous studies and the exclusion of patients who had a stroke during this time. Therefore, it is uncertain how urgently TIA patients should be assessed. We used data from the Oxford Community Stroke Project (OCSP) to estimate the very early stroke risk after a TIA and investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
169
7
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(194 citation statements)
references
References 12 publications
6
169
7
12
Order By: Relevance
“…[99][100][101][102][103][104][105][106] In patients with ischemia in the territory of a stenotic carotid artery, CEA within the first 2 weeks reduces the risk of stroke, 35,93 but the benefit of surgery diminishes with time after the initial event. 107 Transient monocular blindness (amaurosis fugax) is caused by temporary reduction of blood flow to an eye.…”
Section: Clinical Assessment Of Patients With Focal Cerebral Ischemicmentioning
confidence: 99%
“…[99][100][101][102][103][104][105][106] In patients with ischemia in the territory of a stenotic carotid artery, CEA within the first 2 weeks reduces the risk of stroke, 35,93 but the benefit of surgery diminishes with time after the initial event. 107 Transient monocular blindness (amaurosis fugax) is caused by temporary reduction of blood flow to an eye.…”
Section: Clinical Assessment Of Patients With Focal Cerebral Ischemicmentioning
confidence: 99%
“…12 The estimated risk of repeat cerebral events observed in this study was slightly higher than the risk of recurrent stroke observed in previous studies. 5,6 Furthermore, the risk factor analysis in the current study showed that elderly patients waiting longer for surgery are more likely to suffer from repeat cerebral events. This supports the view that repeat events are likely to have different predictive factors and early recognition of these may be useful in preventing any delays in carotid intervention.…”
Section: Discussionmentioning
confidence: 55%
“…5 The Oxford Community Stroke Project (OCSP) reported a stroke risk of 8.6% at 7 days and 12% at 1 month after first-ever TIA and 2.4% in the first week after referral rising to 4.9% at 1 month. 6 As a result, timing of carotid endarterectomy following cerebral ischaemic event has been a topic of considerable interest. [7][8][9][10][11] Carotid endarterectomy is beneficial in reducing risk of stroke in the presence of > 70% carotid stenosis, 3,4 with greater absolute risk reduction seen if surgery is carried out within 1-2 weeks of the ischaemic event.…”
mentioning
confidence: 99%
“…Previous studies have estimated this risk to be 4%-10% within 7 days of TIA, and increases to 8%-12% by 90 days. [3][4][5][6][7][8][9][10][11][12] Stroke is a serious and significant health and economic burden, because it is the leading cause of adult disability, the second leading cause of dementia, and the third leading cause of death. [13][14][15] In addition, it results in the use of large amounts of health care system resources.…”
Section: Introductionmentioning
confidence: 99%